ARCHITECTURAL AND SPATIAL ORGANIZATION OF A SINGLE COMPLEX OF STATIONS OF THE VOLOGDA-ARKHANGELSK RAILWAY IN THE LATE 19TH – EARLY 20TH CENTURY - Petukhova Nina M. (Architecton: Proceedings of Higher Education, 2022)
This article is based on the results of a comprehensive study involving the architectural complex of the 600 km Vologda-Arkhangelsk line, Northern Railway, carried out for the first time covering all of its 19 stations. The study covered the history of the station complex in the period of 1894-1900s designed by the architect Lev Kekushev together with I.A. Ivanov-Shitz, which was constructed simultaneously with the railway under the leadership of S.I. Mamontov. The composition and arrangement of the stations along the railway were examined along with their typological composition, and planning, spatial and stylistic characteristics, which determine uniform perception of the entire complex of stations. The main features and development principles of the railway’s architectural complex were established at various urban planning levels - from the location of the stations along the railway to the architectural and spatial treatment of the stations themselves.